Pengaruh Kulit Umbi Ketela Pohon (Manihot utilissima Crantz.) pada Media Tanam terhadap Pertumbuhan dan Produksi Buah Tanaman Tomat (Lycopersicum esculentum Mill.) - , MITA OCTAVIANI, Drs. Sudjino M. S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tomato (Lycopersicum esculentum Mill.) is one of the very important agricultural commodities. Right now, a lot of people need to eat tomatoes. One of the efforts to meet the needs of the tomatoes by doing planting tomatoes in your own home.Fertilizer is one business that is very important in increasing the production of tomatoes. The cassava (Manihot utilissima Crantz.) peel is one of the organic material that can be used as fertilizer. Cassava peels contain a variety of nutrients required by plants like nitrogen, sulfur, phosphorus, and others. The cassava skin also contains a lot of cellulose. However, in the cassava peel contained cyanide acid which can inhibit plant growth. Although it has a high content of cyanide acid, but still could be reduced by doing some processing ways, among others, by cutting and drying or aerated.Therefore, this research aims to study the response of growth and yield of tomato plants against the granting of the cassava peels cut, smooth of cassava peels (cassava peels flour), and cassava peels extract at dose 500 g/5 kg of soil, 1000 g/5 kg of soil, and 1500 g/5 kg of soil. The method used is to mix up the land on which the media with pieces of cassava peels, cassava flour, and cassava peels extract. Each of the media grows planted with one stem tomato plant. Measured parameters include length of plants, number of branches, number of leaves, dry weight (root, stem, and leaf), number of pieces, weight of fruit, and the volume of the fruit.The results obtained are then made into a graph, and then tested with the ANOVA test of significance of 5%. Results obtained from this research that pieces of the cassava peels is the most good in improving growth and yield of tomato plants. In addition, the granting of cassava peels at a dose of 500 g/5 kg soils also shows the best results in improving growth and yield of tomato plants.